Dark Current mechanisms in quantum dot laser structures - Hasbullah, Nurul Fadzlin; David, J. P. R.; Mowbray, D. J. (American Institute of Physics, 2011)
Current-voltage measurements have been performed on InAs/InGaAs/GaAs quantum dot structures with varying growth and design parameters. These measurements show that the forward and reverse bias dark currents decrease with increasing spacer growth temperature, however, they are relatively insensitive to the number of periods of the quantum dot layers. Temperature dependent current-voltage measurements show that the mechanism that governs the reverse bias leakage current is due to generation-recombination via mid-band traps assisted by the Frenkel-Poole emission of carriers from these traps.